Explaining Employee Motivation and Risk-Taking Propensity on Quality of Work-life among Nurses in Mowe, Nigeria: Menjelaskan Motivasi Karyawan dan Kecenderungan Mengambil Risiko terhadap Kualitas Kehidupan Kerja di Kalangan Perawat di Mowe, Nigeria - Okurame, David E.; Daramola , Gbeminyi; Uye, Emmanuel E. (Psikologia : Jurnal Psikologi, 2025)
Nursing profession constitutes a risk-laden occupation that affects quality of work life. Study linking motivation and risk-taking propensity among nurses in suburban Nigeria is scare. Therefore, this study examined employee motivation and risk-taking propensity as predictors of quality of work life among nurses in Mowe, Ogun State, Nigeria. A cross-sectional survey design was adopted while purposive sampling technique was used to select two health facilities. Data were collected from 239 nurses using validated scales. Three research questions were generated and tested using t-test of independent samples and multiple regressions analysis at a p < .05 level of significance. The result revealed that employee motivation [t (237) = 1.98, p < 0.05] and risk-taking propensity [t(237)=5.01, p < 0.05] significantly influenced quality of work life among nurses. Also, employee motivation and risk propensity jointly predicted quality of work life among nurses [R2 = 0.17, F (2,236) =24.57, p = 0.05]. Finally, employee motivation (β = 0.22, p < 0.05) and risk-taking propensity (β=.31, p < 0.05) independently predicted quality of work life among nurses. The study concluded that employee motivation and risk-taking propensity are excellent predictors of quality of work life among nurses. It is recommended that the hospital administrators should put in place robust welfare package that would help to sustain quality of work life among nurses. Highlights: Significant Predictors – Both motivation and risk-taking propensity significantly influence nurses' quality of work life. Joint and Independent Effects – These factors jointly and independently predict work life quality, explaining 17% of its variance. Practical Recommendation – Hospital administrators should enhance welfare packages to improve nurses' quality of work life. Keywords: Motivation, Risk-Taking Propensity, Quality Of Work Life, Nurses, Mowe /Nigeria